Role of the Epigenetic Modifier JMJD6 in Tumor Development and Regulation of Immune Response - Wang, Kai; Yang, Chao; Li, Haibin; Liu, Xiaoyan; Zheng, Meiling; Xuan, Zixue; Mei, Zhiqiang; Wang, Haiyong (Frontiers in Immunology, 2022)
JMJD6 is a member of the Jumonji (JMJC) domain family of histone demethylases that contributes to catalyzing the demethylation of H3R2me2 and/or H4R3me2 and regulating the expression of specific genes. JMJD6-mediated demethylation modifications are involved in the regulation of transcription, chromatin structure, epigenetics, and genome integrity. The abnormal expression of JMJD6 is associated with the occurrence and development of a variety of tumors, including breast carcinoma, lung carcinoma, colon carcinoma, glioma, prostate carcinoma, melanoma, liver carcinoma, etc. Besides, JMJD6 regulates the innate immune response and affects many biological functions, as well as may play key roles in the regulation of immune response in tumors. Given the importance of epigenetic function in tumors, targeting JMJD6 gene by modulating the role of immune components in tumorigenesis and its development will contribute to the development of a promising strategy for cancer therapy. In this article, we introduce the structure and biological activities of JMJD6, followed by summarizing its roles in tumorigenesis and tumor development. Importantly, we highlight the potential functions of JMJD6 in the regulation of tumor immune response, as well as the development of JMJD6 targeted small-molecule inhibitors for cancer therapy.